Westminster Trades Council - Production Memorandum, 1 October 1942 (page 1) (1942)
1942 1939-1945 "Westminster Trades Council - Production Memorandum, 1 October 1942 (page 1)" [T0234a.jpg], 1942 Local trades councils were involved in a wide range of community issues during the war. This document deals with food distribution, shopping, part time employment children, nurseries, communal feeding, school meals, transport and entertainment.